Fungsi Peranan Pendidikan Dan Pelatihan Terhadap Peningkatan Keterampilan Kinerja Karyawan Di Perusahaan - Ahya Nurdin; Dety Mulyanti (Universitas 17 Agustus 1945 Semarang, 2023)
Education and training have a strategic role in improving the quality of human resources, namely civil servants who are professional both in terms of competence, attitude and expected behavior in accordance with their respective duties and roles. The objectives of education and training have an influence on employee performance, this can be seen from the objectives of the training which are in line with performance measurement indicators. The purpose of this theoretical review is to find out how the functions and roles of education and training affect the improvement of employee performance skills in companies. The method used is a theoretical review by analyzing and comparing existing theories. The results of this theoretical review are in carrying out the roles and functions of education and training to improve employee performance skills by increasing human resources, advancing science and technology, and increasing the quality development of company quality. It can be concluded that the role and function of education and training is an activity of a company that intends to be able to improve and develop attitudes, behavior, skills and knowledge of employees in accordance with the wishes of the company in improving employee performance. For agencies or companies, it is also necessary to encourage the development of the basic capabilities of existing employees. The education and training carried out by the company is beneficial for the company, employees, and improves performance and performance in good quality.